2021
DOI: 10.1186/s13643-021-01814-2
|View full text |Cite
|
Sign up to set email alerts
|

Systematic reviews of observational studies of Risk of Thrombosis and Bleeding in General and Gynecologic Surgery (ROTBIGGS): introduction and methodology

Abstract: Background Venous thromboembolism (VTE) and bleeding are serious and potentially fatal complications of surgical procedures. Pharmacological thromboprophylaxis decreases the risk of VTE but increases the risk of major post-operative bleeding. The decision to use pharmacologic prophylaxis therefore represents a trade-off that critically depends on the incidence of VTE and bleeding in the absence of prophylaxis. These baseline risks vary widely between procedures, but their magnitude is uncertain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 65 publications
0
29
0
Order By: Relevance
“…In the supplementary material (table S13), we have provided examples of these calculations of baseline risks for symptomatic venous thromboembolism specific to the surgery or procedure; most were obtained from an ongoing systematic review of observational studies. 57 conclusions We showed that direct oral anticoagulants and LMWH probably reduce symptomatic venous thromboembolism in major non-cardiac surgery, and that direct oral anticoagulants probably have a relatively greater efficacy than LMWH at the standard prophylactic dose. All of the drug treatment options probably increase bleeding.…”
Section: Study Implications For Research and Practicementioning
confidence: 68%
See 1 more Smart Citation
“…In the supplementary material (table S13), we have provided examples of these calculations of baseline risks for symptomatic venous thromboembolism specific to the surgery or procedure; most were obtained from an ongoing systematic review of observational studies. 57 conclusions We showed that direct oral anticoagulants and LMWH probably reduce symptomatic venous thromboembolism in major non-cardiac surgery, and that direct oral anticoagulants probably have a relatively greater efficacy than LMWH at the standard prophylactic dose. All of the drug treatment options probably increase bleeding.…”
Section: Study Implications For Research and Practicementioning
confidence: 68%
“…Decision makers can use our network relative treatment effects and combine them with trustful (and ideally up-to-date) baseline risk estimates specific to their population and surgery, to obtain absolute treatment effects for benefits and harms. In the supplementary material (table S13), we have provided examples of these calculations of baseline risks for symptomatic venous thromboembolism specific to the surgery or procedure; most were obtained from an ongoing systematic review of observational studies 57…”
Section: Discussionmentioning
confidence: 99%
“…Methods to evaluate the RoB in longitudinal cohort studies are less developed than the methods in randomized trials. 43 Through discussion and consensus building, and considering previous literature, [7][8][9][44][45][46] we developed an instrument to categorize RoB of the studies 12 that evaluated each study according to 6 domains: (1i) sampling of the study population, (2) reporting of thromboprophylaxis, (3) source of information, (4) whether a majority of patient recruitment years were earlier or later than 2010, (5) clear specification of duration of follow-up, and (6) study type (Supplemental Digital Content Appendix, page 146, Supplemental Digital Content 1, http://links.lww.com/SLA/E826). For each domain, we judged studies to have either a high or low RoB, classifying studies as follows: no high RoB domains as very low, 1 high RoB domain as low, 2 high RoB domains as moderate, and 3 or more high RoB domains as high overall RoB.…”
Section: Risk Of Bias and Assessment Of The Evidence Certaintymentioning
confidence: 99%
“…The main cause of death in middle-and high-income world regions is represented by cardiovascular diseases, as the World Health Organization (WHO) indicated. In developed countries, venous thromboembolic (VTEs) events ARE considered the third most common cardiovascular disease after coronary heart disease and stroke, with one case per The articles' research was performed following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses [20].…”
Section: Introductionmentioning
confidence: 99%